Acute perforated appendicitis due to metastatic small-cell lung cancer - Keramidaris, Dimitrios; Oikonomou, Christianna; Theodorolea, Kyriaki; Mohamed, Tahira; Mohamed, Tahira (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Keramidaris D, Oikonomou C, Theodorolea K, Mohamed T, Gourgiotis S. Acute perforated appendicitis due to metastatic small-cell lung cancer. Turk J Gastroenterol 2019; 30(11): 993-4.